2016
DOI: 10.1016/j.jhealeco.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Choice of hospital: Which type of quality matters?

Abstract: HighlightsPatients choose hospitals that improve their self-reported health.Quality, as measured by readmission and mortality rates, is less important.Healthier patients are more willing or able to travel for higher quality.Quality competition in the English NHS is possible.Potential for competition declines rapidly with distance between hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(147 citation statements)
references
References 63 publications
9
129
1
8
Order By: Relevance
“…We argue that, although current outcomes are potentially influenced by rival's current outcomes (or possibly last-period outcomes), adjustment is sufficiently rapid that current outcomes are not affected by what rivals were doing 2 or 3 years previously. Some studies on the English NHS (Gaynor, Propper, & Seiler, 2012;Gutacker, Siciliani, Moscelli, & Gravelle, 2016;Sivey, 2012) show that patients choose hospitals with higher quality and lower waiting times. For example, Gutacker, Siciliani, Moscelli, and Gravelle (2016) find that the demand of a hospital decreases by 0.63% if a rival located within 10 km increases its PROMs quality by 1%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that, although current outcomes are potentially influenced by rival's current outcomes (or possibly last-period outcomes), adjustment is sufficiently rapid that current outcomes are not affected by what rivals were doing 2 or 3 years previously. Some studies on the English NHS (Gaynor, Propper, & Seiler, 2012;Gutacker, Siciliani, Moscelli, & Gravelle, 2016;Sivey, 2012) show that patients choose hospitals with higher quality and lower waiting times. For example, Gutacker, Siciliani, Moscelli, and Gravelle (2016) find that the demand of a hospital decreases by 0.63% if a rival located within 10 km increases its PROMs quality by 1%.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies on the English NHS (Gaynor, Propper, & Seiler, 2012;Gutacker, Siciliani, Moscelli, & Gravelle, 2016;Sivey, 2012) show that patients choose hospitals with higher quality and lower waiting times. For example, Gutacker, Siciliani, Moscelli, and Gravelle (2016) find that the demand of a hospital decreases by 0.63% if a rival located within 10 km increases its PROMs quality by 1%. Hospitals are therefore unlikely to delay their reaction to changes in rivals' performance by 2 or 3 years in order to avoid reductions in the volume of patients treated and, hence, revenue.…”
Section: Methodsmentioning
confidence: 99%
“…There is some literature to suggest that consumers (Phillips et al 2007) or payers (Robinson and MacPherson 2012) use published facility-level quality information when selecting facilities to use or include in preferred networks, if the information is easy to absorb and focused on identifying the "best and worst" quality providers. Though mixed, the literature suggests that competition among hospitals is associated with improvement in several observable indicators of hospital quality (Bloom et al 2015;FTC and DOJ 2014;Gaynor and Vogt 2000;Gutacker et al 2016). Similarly, greater competition among nursing home providers tends to be associated with higher quality (Grabowski and Hirth 2003;Grabowski and Town 2011;Huang and Hirth 2016).…”
Section: Competition and Qualitymentioning
confidence: 99%
“…Nevertheless, the emphasis of the most recent literature has been on measures of clinical quality. For instance, Gutacker et al (2016) find that hospital demand is responsive to observed quality for hip replacement surgery in the United Kingdom. Similarly, in their analysis of hip replacement surgeries in the United Kingdom, Beckert et al (2012) reveal that hospital demand increases with clinical quality.…”
Section: öZetmentioning
confidence: 99%